2020
DOI: 10.1016/j.omto.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Inhibitor, OGP46, Is Effective against Imatinib-Resistant BCR-ABL Mutations via the BCR-ABL/JAK-STAT Pathway

Abstract: Chronic myeloid leukemia (CML) is caused by the Philadelphia (Ph + ) chromosome carrying the BCR-ABL oncogene, a constitutively active tyrosine kinase. The discovery of imatinib represents a major success story in the treatment against CML. However, mutations in the BCR-ABL kinase domain are a major cause of resistance to imatinib, demonstrating that BCR-ABL remains a critical drug target. Here, we investigate a novel small molecule inhibitor, OGP46, for its inhibitory activity against K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Oridonin was a component of the Rabdosia rubescens , a traditional Chinese Medicine, which was effective on 31 cases of primary liver cancer by the clinical observation. As described in our previous work ( Wei et al, 2020 ), OGP46 has been shown to induce cell differentiation and inhibit the cell proliferation of chronic myeloid leukemia (CML) cell lines expressing native BCR-ABL and mutant BCR-ABL, including T315I through the BCR-ABL/JAKSTAT pathway by depleting the BCR-ABL oncogene. Moreover, OGP46 was less toxic to normal blood mononuclear cells.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Oridonin was a component of the Rabdosia rubescens , a traditional Chinese Medicine, which was effective on 31 cases of primary liver cancer by the clinical observation. As described in our previous work ( Wei et al, 2020 ), OGP46 has been shown to induce cell differentiation and inhibit the cell proliferation of chronic myeloid leukemia (CML) cell lines expressing native BCR-ABL and mutant BCR-ABL, including T315I through the BCR-ABL/JAKSTAT pathway by depleting the BCR-ABL oncogene. Moreover, OGP46 was less toxic to normal blood mononuclear cells.…”
Section: Introductionmentioning
confidence: 82%
“…Our previous study had found that OGP46 exhibited potent activity against CML cell lines by inducing cell differentiation ( Wei et al, 2020 ). In this study, we discovered that OGP46 induced cell-cycle arrest at the G1/G0 phase and caused inhibition of cell proliferation by inducing cell differentiation in HL-60, NB4, and Kasumi-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mRNA-Sequencing (mRNA-seq) was performed for MOLM-13 and THP-1 cells. As described in a previous work [12], after incubating with JOA for 48 h, cells were collected for RNA extraction. Sequencing libraries were prepared and then sequenced using 150 bp pair-end strategies with an Illumina HiSeq X10 instrument (Annoroad Genomics, Beijing, China).…”
Section: Mrna-sequencing Analysismentioning
confidence: 99%